2005
DOI: 10.1159/000085819
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Gene Polymorphism and Personality Traits in a Korean Population

Abstract: Recently, there has been growing enthusiasm for exploring biological approaches to personality, especially in the area of genetic research into the identification of those genes responsible for particular personality traits. The aim of this study was to investigate the association between the serotonin transporter-linked promoter region (5-HTTLPR) polymorphism and personality traits. We recruited 211 unrelated, normal subjects. The Korean version of the Temperament and Character Inventory (TCI) was used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
(31 reference statements)
3
13
2
1
Order By: Relevance
“…The genotypic distributions of the 5-HTTLPR, TPH1 and MAOAEcoRV polymorphisms are similar to those presented in other studies of Korean populations [28][29][30] . As the number of subjects with the l/l genotype of 5-HTTLPR in our sample was small (8 males, 4.4%; 9 females, 7.2%), and as the s allele has the lower transcription activity, the l/s and l/l genotypes were grouped together into a non-s/s genotype group for comparison with the s/s genotype.…”
Section: Resultssupporting
confidence: 85%
“…The genotypic distributions of the 5-HTTLPR, TPH1 and MAOAEcoRV polymorphisms are similar to those presented in other studies of Korean populations [28][29][30] . As the number of subjects with the l/l genotype of 5-HTTLPR in our sample was small (8 males, 4.4%; 9 females, 7.2%), and as the s allele has the lower transcription activity, the l/s and l/l genotypes were grouped together into a non-s/s genotype group for comparison with the s/s genotype.…”
Section: Resultssupporting
confidence: 85%
“…The results of both cited studies are inconsistent with the results that we obtained. It must be remembered, however, that the frequency of occurrence of the S variant in Asian populations is totally different from that in the Polish population [33,34] . Moreover, although the endurance and persistence parameters, as understood by Cloninger, are correlated, they are not identical.…”
Section: Discussionmentioning
confidence: 89%
“…For example, at the genetic level, carrying the " short " allele of the serotonin transporter (5 -HTT) polymorphism gene has been linked to high reactivity and shyness in children . It has been suggested that the short allele might be more prevalent in East Asian populations and the long allele more prevalent in European populations (Kim et al, 2005 ).…”
Section: Prevalence Of S Hyness and S Ocial W Ithdrawalmentioning
confidence: 99%